Geomorhological, Sedimentological and Magnetic Susceptibility Analysis of sediments in the "Mikro" Eptamilon cave, Serres, Greece - Πεχλιβανίδου Σ.; Αηδονά E.; Βουβαλίδης Κ.; Πέννος Χ.; Αλμπανάκης Κ. (Bulletin of the Geological Society of Greece, 2011)
In the area of Eptamili Village, located at the foothills of the southern-eastern part of Mount Menoikio (Serres Prefecture, Northern Greece) two underground karst cavities were revealed during the works of marble exploitation, named as ‘Mikro’ and ‘Megalo’ Cave of Eptamilon. At the entrance of the ‘Mikro’ Cave there is a naturally deposited sequence of clastic sediments alternating with chemical deposits with a thickness of 2m, lying uncomfortably on the bedrock marbles. In order to investigate the depositional processes and conditions and to understand the palaeoenvironmental changes during the cave evolution, grain size analysis and magnetic measurements were conducted on sediment samples from the sedimentary sequence. Grain size analysis showed the presence of fine sandy beds alternating with silty and clayey layers. This structure correlates with the magnetic signature of the sediments and especially the magnetic susceptibility (xlf) and the frequency depended magnetic susceptibility (xfd), conducting conclusions concerning the palaeoclimatic conditions and the velocity of the flow during the time of deposition of the sedimentary sequence. This study suggest the use of environmental magnetism as an independent methodology in palaeoenvironmental studies.